The Practicing of Parliamentary Democracy in Federal Nepal - Shah, Abrita; Bam, Chakra (Journal of Development Review, 2023)
This article assesses how the parliamentary democracy (PD) in federal Nepalworks. Nepal's federal parliament spent six years, but the notion and practice of PD are gradually fading. It descriptively analyzes the condition of cabinet, the parliament session, the role of the opposition parties, and the motion of confidence. The federal parliament practices the old-fashioned types political culture and the absence of democratic traits. The House session works for 364 days within 43 times meeting adjourned. The federal parliament also faced two times parliament dissolutions and one time PM failed to secure the vote of motion. Likewise, 41 times cabinet had been reshuffled and lower representation of women ministers. More than 50 times federal parliament obstructed, protested, and encircled. It studies qualitative methods of descriptive and analytical design. The source of data is secondary. Hence, this paper concludes that the practice of PD in the federal parliament survived but no reasonable outcomes were achieved.